THE CURRENT SITUATION OF MASTICATORY BEHAVIOR OF FIRST GRADER AT ELEMENTARY SCHOOL: A RELATIONSHIP BETWEEN MASTICATORY ABILITY AND STUDENTS’ LIKES AND DISLIKES - Sakuma, Naomi; Aiba, Naomi; Kawamura, Momoyo; Katayama, Ryosuke; Takao, Hidenobu (PEOPLE: International Journal of Social Sciences, 2020)
Twenty percent of first-graders of a public elementary school in Kanagawa Prefecture were unable to masticate school lunch properly. Teachers encouraged masticate training at school, but it showed no improvement. The purpose of this research was to investigate the characteristics of mastication to find possible methods and more specific mastication education. The subjects were 100 first graders(6～7years old) at public elementary school where school lunch was served with an individual tray. The survey was conducted during school lunchtime by recording the bread crust eating situation. Every student was provided with 8g of bread crust cut into three equal parts. Within one month, on the days when kibinago (herring-like forage fish), cabbage, potatoes, curry rice, bonito, and komatsuna (Japanese Spinach) were served, the subjects were asked about their “Likes or Dislikes” and the food was “Easy to Masticate or Hard to Masticate”.The average of masticatory time during eating bread crust was 76 seconds, the maximum was 151 seconds, and the minimum was 19 seconds. The average of masticatory frequency was 72 times, the maximum was 155 times and the minimum was 27 times. The average masticatory speed was 58 beats per minute (bpm), the fastest was 113 bpm and the slowest was 29 bpm. The most favorite dish was curry rice (99%) and the least favorite dishes were kibinago and bonito (13%, respectively). The highest percentage (27%) of the subjects answered bonito dish as “Hard to Masticate” and the lowest percentage (1%) was curry rice. “Dislike” was significantly associated with “Hard to Masticate” in cabbage (p<0.01) and bonito (p<0.01). The first graders had individual differences in masticatory behavior. It was suggested that “Likes and Dislikes” are related to masticatory ability. If the children practice the mastication of solid foods before entering school, the children might eat more smoothly.